Q&A - Ask Doubts and Get Answers
Q

Chapter 2 - Polynomials Exercise 2.5 12

12. Verify that    x^3 + y^3 + z^3 -3xyz = \frac{1}{2} ( x + y + z)\left[(x-y)^2 + (y-z)^2 + (z-x)^2 \right ]

Answers (1)
Views
R Riya

We know that

x^3+y^3+z^3-3xyz = (x+y+z)(x^2+y^2+z^2-xy-yz-zx)

Now, multiply and divide the R.H.S. by 2

x^3+y^3+z^3-3xyz = \frac{1}{2}(x+y+z)(2x^2+2y^2+2z^2-2xy-2yz-2zx)

                                            = \frac{1}{2}(x+y+z)(x^2+y^2-2xy+x^2+z^2-2zx+y^2+z^2-2yz)

                                            = \frac{1}{2}(x+y+z)\left((x-y)^2+(y-z)^2 +(z-x)^2\right )                                        \left(\because a^2+b^2-2ab=(a-b)^2 \right )

Hence proved 

Exams
Articles
Questions